2018
DOI: 10.1007/s40618-018-0856-6
|View full text |Cite
|
Sign up to set email alerts
|

Components of metabolic syndrome in relation to plasma levels of retinol binding protein 4 (RBP4) in a cohort of people aged 65 years and older

Abstract: PurposeElevated plasma concentration of retinol binding protein 4 (RBP4) has recently emerged as a potential risk factor as a component of developing metabolic syndrome (MS). Therefore, this study aimed to analyse the relationship between components of MS and concentrations of plasma RBP4 in a population of subjects 65 years and older.MethodsThe study sample consisted of 3038 (1591 male) participants of the PolSenior study, aged 65 years and older. Serum lipid profile, concentrations of RBP4, glucose, insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
2
16
0
1
Order By: Relevance
“…In the Korek et al study, RBP4 levels did not correlate with BMI or fat mass and did not differ between individuals with obesity and those without obesity-RBP4 levels in both groups were 33.93 ± 4.46 and 32.53 ± 2.53 µg/mL, respectively [64]. Similar results were reported by other authors [65][66][67][68]. On the other hand, certain studies demonstrate increased RBP4 concentrations among individuals with obesity, as well as the association between RBP4 and BMI [36,69].…”
Section: Rbp4 Obesity and Metabolic Syndromesupporting
confidence: 76%
See 2 more Smart Citations
“…In the Korek et al study, RBP4 levels did not correlate with BMI or fat mass and did not differ between individuals with obesity and those without obesity-RBP4 levels in both groups were 33.93 ± 4.46 and 32.53 ± 2.53 µg/mL, respectively [64]. Similar results were reported by other authors [65][66][67][68]. On the other hand, certain studies demonstrate increased RBP4 concentrations among individuals with obesity, as well as the association between RBP4 and BMI [36,69].…”
Section: Rbp4 Obesity and Metabolic Syndromesupporting
confidence: 76%
“…Moreover, in the study by Karamfilova et al, RBP4 levels ≥55 mcg/mL were associated with a 3.1 higher risk of developing metabolic syndrome [74]. Other studies also have confirmed the relationship between the components of metabolic syndrome and RBP4 levels [65,66]. Additionally, RBP4 can also be a predictor for the diagnosis of metabolic syndrome and weight regain [70,74,75].…”
Section: Rbp4 Obesity and Metabolic Syndromementioning
confidence: 90%
See 1 more Smart Citation
“…The factors consistently associated with RBP4 levels both pre-therapy in CHC patients and at 24 weeks post-therapy in SVR patients, such as BMI, TG, and eGFR, disclosed their fundamental links of RBP4, regardless of HCV infection. For example, BMI has an independent association with RBP4 levels in Asian men [ 30 ]; TG level is related to RBP4 level of participants ≥65 years [ 31 ] and is the strongest predictor of RBP4 levels in morbidly obese patients [ 32 ]; and eGFR is negatively associated with RBP4 levels [ 10 , 33 ]. By contrast, the pre-therapy-only factors of CHC patients such as NLR and age, and the post-therapy-only factors of SVR patients such as sex, uric acid, and FIB-4 levels suggested their potential links, direct or indirect, between HCV infection and RBP4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, both the HCV-infected and mammalian expression construct encoding HCV core Huh7.5 cells showed increased RBP4 levels [ 43 ], and our HCV core transgenic mice with nonobese simple steatosis showed higher hepatic RBP4 expression and higher serum RBP4 and TG levels than the non-HCV core transgenic littermates. Given that plasma RBP4 levels correlated positively with hepatic fat [ 8 ] and serum TG levels [ 31 , 32 , 44 ], and prominent lipid vacuoles were noted in the RBP4-positive hepatocytes of the HCV core transgenic mice, it is convincible that simple steatosis with concurrent hypertriglycemia would lead to increase in RBP4 levels, regardless of HCV infection. Steatosis thus is an HCV-related, but not a HCV-specific factor for RBP4 levels.…”
Section: Discussionmentioning
confidence: 99%